Interactive effects of dietary vitamin K3 and Bacillus subtilis PB6 on the growth performance and tibia quality of broiler chickens with sex separate rearing. (14th February 2020) - Guo, S.; Xv, J.; Li, Y.; Bi, Y.; Hou, Y.; Ding, B.
Abstract : Both vitamin K and probiotics can promote the bone health of poultry and mammals. The present study was conducted to investigate the interactive effects between vitamin K3 (VK3 ) and Bacillus subtilis PB6 on the growth performance and tibia quality of broiler chickens with sex separate rearing. In a 3 × 2 × 2 factorial arrangement, 720 one-day-old broiler chicks (Arbor Acres) were assigned to 12 groups with three levels of dietary VK3 (0, 0.5 and 4.0 mg/kg), with or without probiotic supplementation (500 g/t) and with sex separation (male and female). Each group included 3 replicates with 20 birds per replicate. During day 1 to 21, 0.5 and 4.0 mg/kg of VK3 increased average daily gain (ADG ) of all birds and average daily feed intake of male birds ( P < 0.05). During day 22 to 42, probiotic supplementation increased the ADG of birds ( P < 0.05). Probiotic addition increased the weight, length, diameter and strength of tibia in all birds, and 0.5 and 4.0 mg/kg of VK3 increased the tibial breaking strength of male birds at day 21 ( P < 0.05). Vitamin K3 and probiotic synergistically increased tibial breaking strength at day 42 and ash content at day 21 ( P < 0.05). Three factors exhibited interactive effects on the chemical composition of tibia at day 42, and female birds fed 4 mg/kg of VK3 and probiotic had the highest contents of ash, calcium and phosphorus ( P < 0.05). Bacillus subtilis PB6 increased the serum phosphorus level of male birds at day 21 and serum calcium level of female ones at day 42 ( P < 0.05). At day 21, in the probiotic-supplemented birds, serum osteocalcin (OCN ) and bone-specific alkaline phosphatase (BALP ) were increased by 0 and 4.0 mg/kg of VK3, respectively ( P < 0.05). Probiotic increased serum OCN and cooperated with VK3 to increase the serum BALP at day 42 ( P < 0.05). Vitamin K3 and probiotic synergistically down-regulated the mRNA expression of Runt-related transcription factor 2 and OCN at day 21 ( P < 0.05). Vitamin K3 down-regulated the alkaline phosphatase (liver/bone/kidney) expression in male birds at day 21 and 42, but probiotic up-regulated the expression of these genes at day 42 ( P < 0.05). In conclusion, VK3 and B. subtilis PB6 promoted the growth performance of broilers during starter and grower phases, respectively. They synergistically improved the physical and chemical traits of tibias, especially in grower phase, by modulating calcium and phosphorus metabolism as well as osteogenic gene expression.